Bioelectromagnetic medicine: The role of resonance signaling. (December 2013) - Foletti, Alberto; Grimaldi, Settimio; Lisi, Antonella; Ledda, Mario; Liboff, Abraham R.
<x xml:space="preserve">Abstract</x> Only recently has the critical importance of electromagnetic (EM) field interactions in biology and medicine been recognized. We review the phenomenon of resonance signaling, discussing how specific frequencies modulate cellular function to restore or maintain health. The application of EM-tuned signals represents more than merely a new tool in information medicine. It can also be viewed in the larger context of EM medicine, the all-encompassing view that elevates the EM over the biochemical. The discovery by Zhadin that ultrasmall magnetic intensities are biologically significant suggests that EM signaling is endogenous to cell regulation, and consequently that the remarkable effectiveness of EM resonance treatments reflects a fundamental aspect of biological systems. The concept that organisms contain mechanisms for generating biologically useful electric signals is not new, dating back to the nineteenth century discovery of currents ofinjury by Matteucci. The corresponding modern-day version is that ion cyclotron resonance magnetic field combinations help regulate biological information. The next advance in medicine will be to discern and apply those EM signaling parameters acting to promote wellness, with decreasing reliance on marginal biochemical remediation and pharmaceuticals.